2011
DOI: 10.1016/j.cmpb.2010.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Systematic method to assess microvascular recruitment using contrast-enhanced ultrasound. Application to insulin-induced capillary recruitment in subjects with T1DM

Abstract: Contrast-enhanced ultrasound (CEU) is an ultrasound imaging technique used to assess tissue perfusion. Analysis of microvascular recruitment necessitates the definition of a region of interest (ROI) containing exclusively the tissues to be studied. Conventional ROI selection requires examining the images and drawing the ROI by hand, making the analysis of CEU images non-reproducible and analyst-dependent. We have designed a systematic ROI selection method that is both reproducible and analyst-independent. Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In the study of Lindner et al [31], the combined angiographic severity score correlated with exercise blood flow (r=0.70, P =0.003) and flow reserve (r=0.56, P =0.047) in non-diabetic individuals with peripheral artery disease but not in diabetic peripheral artery disease patients. Chan et al [24] found that diabetic microvascular complications were significantly correlating with the effect of supraphysiological insulin levels on capillary recruitment or de-recruitment in patients with type 1 diabetes. Thus, supraphysiological insulin levels increased MBV in individuals with low insulin sensitivity and increased microvascular complications but decreased MBV in individuals with high insulin sensitivity and increased microvascular complications [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Lindner et al [31], the combined angiographic severity score correlated with exercise blood flow (r=0.70, P =0.003) and flow reserve (r=0.56, P =0.047) in non-diabetic individuals with peripheral artery disease but not in diabetic peripheral artery disease patients. Chan et al [24] found that diabetic microvascular complications were significantly correlating with the effect of supraphysiological insulin levels on capillary recruitment or de-recruitment in patients with type 1 diabetes. Thus, supraphysiological insulin levels increased MBV in individuals with low insulin sensitivity and increased microvascular complications but decreased MBV in individuals with high insulin sensitivity and increased microvascular complications [24].…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al [24] found that diabetic microvascular complications were significantly correlating with the effect of supraphysiological insulin levels on capillary recruitment or de-recruitment in patients with type 1 diabetes. Thus, supraphysiological insulin levels increased MBV in individuals with low insulin sensitivity and increased microvascular complications but decreased MBV in individuals with high insulin sensitivity and increased microvascular complications [24].…”
Section: Discussionmentioning
confidence: 99%
“…To minimize/eliminate the dependence of the ROI selection on the operator and assure consistency in the ROI definition across different sequences, we developed a systematic procedure to select ROI [24]. Briefly, the method is based on the normalization of the intensity of the acoustic signal stored in the image files.…”
Section: Methodsmentioning
confidence: 99%
“…This method requires having the information of the pulsing interval measured in number of heart beats for each frame. We described in [24] an algorithm to reconstruct the pulsing interval in number of heart beats from the relative time (in seconds) when relative time is the only information stored in the file. For each sequence, the ROI was selected based on this systematic method and the mean acoustic intensity over the ROI was fitted to the exponential function described by equation (1) to obtain estimates of the parameters A, β and c.…”
Section: Methodsmentioning
confidence: 99%